2006
DOI: 10.1111/j.1440-1681.2006.04375.x
|View full text |Cite
|
Sign up to set email alerts
|

Early Structural Changes of Aortic Wall in Sinoaortic‐denervated Rats

Abstract: 1. The present work was designed to observe the early structural changes in the aortic wall in Sprague-Dawley rats 1, 2 and 4 weeks after sinoaortic denervation (SAD). 2. Rats were examined 1, 2 and 4 weeks after SAD. Blood pressure (BP) was recorded in the conscious state. The thoracic aortas were taken for investigations, including: light microscopy, electron microscopy, immunohistochemistry and terminal deoxynucleotidyl transferase (TdT)-mediated dUTP nick-end labelling (TUNEL). 3. Blood pressure variabilit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…Experimental data are available showing that baroreflex impairment can cause atheroma through inflammation and endothelial cell changes. 7, 8 Improvement of baroreflex function after low-dose ketanserin has prevented the development of atherosclerosis in rats and rabbits. This effect was independent of ABP lowering.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental data are available showing that baroreflex impairment can cause atheroma through inflammation and endothelial cell changes. 7, 8 Improvement of baroreflex function after low-dose ketanserin has prevented the development of atherosclerosis in rats and rabbits. This effect was independent of ABP lowering.…”
Section: Discussionmentioning
confidence: 99%
“…5, 6 Also, it is possible that impaired BRS can accelerate atherosclerosis through inflammation and endothelial cell changes. 7, 8 Baroreflex and Cerebral Autoregulation of ABP was achieved using a servo-controlled finger plethysmograph (Finapres, Ohmeda, CO, USA for patients with carotid stenosis; and Nexfin, BMI for volunteers). Mean ABP and mean CBF velocities (CBFV) in the MCA were recorded over 10-20 min.…”
mentioning
confidence: 99%
“…SAD was performed in SD rats according to the procedure described by Krieger (1964) with minor modifications (Shen et al, 2006). Briefly, rats were anesthetized with a mixture of ketamine and diazepam (i.p.)…”
Section: Preparation Of Sinoaortic Denervation (Sad)mentioning
confidence: 99%
“…In hypertensive rats, the target organ damage correlates negatively with ABR function [10,25] . Interruption of ABR by sinoaortic denervation induced aortic and cardiac hypertrophy independent of the mean level of blood pressure [26][27][28] . In the present study, it was found that dysfunction of the ABR attenuated the circadian expression of clock genes in the SCN.…”
Section: Discussionmentioning
confidence: 93%